Ecological drivers of plant diversity patterns in remnants coastal sand dune ecosystems along the northern Adriatic coastline. Issue 6 (19th June 2018) - Tordoni, Enrico; Napolitano, Rossella; Maccherini, Simona; Da Re, Daniele; Bacaro, Giovanni
Abstract: Coastal sand dunes represent one of the most fragile ecosystems in the Mediterranean basin. These habitats naturally suffer the action of several limiting factors such as sand burial, marine aerosol and low soil fertility; on the other hand, they often host species of high conservation value. Over the last decades, they have also experienced a high level of biological invasion. In this study, we sampled psammophilous vegetation in two sites in the northern Adriatic coast belonging to the Natura 2000 network to describe diversity patterns and to identify the main ecological drivers of species diversity. Plant species richness and their abundance were assessed in each plot. Differences in species composition for native and alien species were compared via PERMANOVA analysis. Species complementarity was explored by partitioning beta diversity in its spatial components (richness and replacement). A Generalized Linear Model was also computed to assess the main environmental factors that may promote invasiveness in these ecosystems. For the investigated area, our results highlight the strong differentiation in community composition both in alien and native species: in particular alien species showed on average a lower complementarity among habitats compared to native species. Specifically, communities seem to be more diversified when larger spatial scales were considered. Beta diversity in both groups appears to be more dominated by the richness component with respect to the replacement component. Furthermore, in these habitats, the occurrence of alien species was shown to be related to geomorphological predictors more than climatic variables.